PEMBENTUKKAN PERILAKU KONSUMSI SISWA MELALUI PEMBELAJARAN EKONOMI - Intan Mayasari, (Pendidikan Ekonomi, 2011)
The study attempts to examine the influence of economics instruction on consumption behavior of eleventh-graders of social science in SMAN 1 Surabaya.  The sample comprised 60 eleventh-graders of social science at  SMAN 1 Surabaya. Data were collected through the use of questionnaire and interview. The data were then analyzed by using simple regression technique. The result of the data analysis shows economics instruction has a significant influence on the consumption behavior by 42.4 %. Other factors excluded from this study affect the consumption behavior by 557.6 %.